Elastofibroma dorsi: a case report of bilateral occurrence and review of literature. Issue 2 (4th March 2021) - De Weerdt, Glenn; Verhoeven, Veronique; Vrints, Ina; Thiessen, Filip; Tondu, Thierry
Abstract: Background: Elastofibroma dorsi (ED) is a benign slow growing soft tissue tumor that is most frequently located subscapular. The prevalence is estimated to be 2% on imaging studies in individuals over 60 years old and might occur bilaterally. The etiology, however, remains unclear. Case presentation: This report presents the case of a man with bilateral ED. He first presented at the age of 49 with a subscapular ED on the right side and again at the age of 53 with a subscapular ED on the left side. At both times, diagnosis of ED was histopathologically confirmed after surgical resection. And, again at both times, the postoperative course was characterized by seroma development. Discussion: This report shows a brief review of literature on ED. It contains a summary of the current data on prevalence, etiology, clinical presentation, diagnosis, histopathological findings, surgical treatment and postoperative management. It also includes a flowchart for diagnostic and therapeutic approach. Conclusions: ED might present bilaterally, though not necessarily affecting both sides simultaneously. In order to diagnose ED MRI is ought to be sufficient. Invasive procedures, i.e. complete surgical excision, are mandatory to treat symptomatic ED, although such surgical procedures are often complicated by seroma formation.